Assessment Of Portfolio Management Skills In Iranian Capital Market Mutual Funds:Baysian Model Averaging Approach - behrang asadi gharehjeloo; hossein abdo tabrizi (پژوهش‌های برنامه و توسعه)
Evaluating portfolio management performance and mutual fund’s active management abilities is of particular importance. Capital asset pricing model and holding portfolios model are among the most important studies to assess the ability of mutual funds market timing and security selection. This study attempts to investigate market timing and security selection ability of Iranian mutual funds during the period of 1393 to 1396. In this research, selected and total mutual funds’ performance in the form of time series and panel data model is evaluated using the combination of capital asset pricing model, including Treynor- Mazuy and Henriksson- Merton, with Fama- French three factor model. In the next step, using holding portfolios model including Kacperczyk and Alda, market timing and security selection ability of mutual funds have been evaluated and related statistics have been extracted. Eventually, using Bayesian Model Averaging approach, by implementing and evaluating numerous models consisting of variables used, posterior probability and probability of the inclusion of each variable in chosen models are presented.